Pengaruh Kualitas Pelayanan, Sanksi Perpajakan, Dan Pengetahuan Perpajakan Terhadap Motivasi Wajib Pajak Orang Pribadi Dengan Sosialiasi Perpajakan Sebagai Variabel Moderating - Difi, Shiva; Arifin, Syamsul Bahri; Hasbulla, Iman Indrafana Kusumo (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze the influence of service quality, tax sanctions and tax knowledge on the motivation of individual taxpayers in paying taxes with tax socialization as a moderating variable at KPP Pratama Medan Polonia. The population in this research is all individual taxpayers registered at KPP Pratama Medan Polonia in 2023, totaling 45,953 taxpayers and the sample is 100 taxpayers. The sampling technique was carried out using a purposive sampling technique by calculating the number of samples using the Slovin formula. The data analysis technique used in this research is Moderated Regression Analysis (MRA) using the SPSS 26 software program tool. The results of research testing show that the variables of service quality, tax sanctions and tax knowledge simultaneously and significantly influence taxpayer motivation. Partially, service quality and tax sanctions have a significant effect on taxpayer motivation, while tax knowledge does not have a significant effect on taxpayer motivation. Tax socialization is able to moderate service quality and tax knowledge on taxpayer motivation. And tax socialization is unable to moderate tax sanctions on taxpayer motivation.